2020
DOI: 10.1039/c9sc05267d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mechanistic investigations of pH-responsive cationic poly(aminoester)s

Abstract: The synthesis and degradation mechanisms of a class of pH-sensitive, rapidly degrading cationic poly(aaminoester)s are described. These reactive, cationic polymers are stable at low pH in water, but undergo a fast and selective degradation at higher pH to liberate neutral diketopiperazines. Related materials incorporating oligo(a-amino ester)s have been shown to be effective gene delivery agents, as the charge-altering degradative behavior facilitates the delivery and release of mRNA and other nucleic acids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 83 publications
(140 reference statements)
2
40
0
Order By: Relevance
“…CARTs spontaneously form NPs upon simple mixing with oligonucleotides or other polyanionic cargos, and CART/mRNA NPs were shown to be effective in pre-clinical studies of vaccines for cancer , and SARS-CoV2 . The modular and efficient synthesis of the CART amphiphiles (eq ) , enabled studies that showed that the nature of the pendant lipid could influence the types of cells that were transfected efficiently. CARTs containing unsaturated lipids exhibited up to 80% transfection of EGFP RNA to lymphocytes …”
Section: Introductionmentioning
confidence: 99%
“…CARTs spontaneously form NPs upon simple mixing with oligonucleotides or other polyanionic cargos, and CART/mRNA NPs were shown to be effective in pre-clinical studies of vaccines for cancer , and SARS-CoV2 . The modular and efficient synthesis of the CART amphiphiles (eq ) , enabled studies that showed that the nature of the pendant lipid could influence the types of cells that were transfected efficiently. CARTs containing unsaturated lipids exhibited up to 80% transfection of EGFP RNA to lymphocytes …”
Section: Introductionmentioning
confidence: 99%
“…sites such as tumors, microenvironment acidification is caused, the application of amino and tertiary amines in the field of drug carriers are promising. [43][44][45] Lang and co-workers successfully grafted amine-terminated ploy(N-isopropylacrylamide) onto poly(2-oxepane-1,5-dione-co-ɛ-caprolactone) to achieve the selfassembled core-shell micelles with biodegradability, thermal response, and pH-response properties. [46] Chen et al successfully developed poly(ethylene glycol)-b-(poly(2-(diethylamino)ethyl methacrylate)-b-poly(hydroxyethyl methacrylate)-g-folic acid) 2 [PEG-b-(PDEAEMA-b-PHEMA-g-FA) 2 ] as a drug carrier, and achieved pH responsiveness owing to the protonation of the tertiary amino groups under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 CARTs are multiblock oligomers consisting of $1 lipid block and a charge-altering block. [38][39][40][41][42][43][44][45] Differing from persistently charged nonviral vectors, CARTs are initially cationic to complex polyanionic nucleic acids but biodegrade under physiological conditions (pH 7.4) to neutral products, facilitating the release of the anionic cargo. 39,44 Here, we demonstrate that CARTs efficiently transfect resting primary human NK cells with messenger RNA (mRNA).…”
Section: Introductionmentioning
confidence: 99%